FACTORS AFFECTING ENTREPRENEURIAL INTENTION THROUGH ENTREPRENEURIAL ATTITUDES AS MEDIATION VARIABLES - Putri, Janeta Naomi; Handoyo, Sarwo Edy (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of entrepreneurship education and the environment on entrepreneurial intentions. This study also aims to determine the mediating effect of entrepreneurial attitudes on the influence of entrepreneurship education on entrepreneurial intentions and the environment on entrepreneurial intentions. The subjects of this study were students studying at Universitas Tarumanagara, majoring in management with a concentration in entrepreneurship. The sample used in this study was 100 respondents. The sample selection technique used in taking respondents is non-probability sampling with a purposive sampling approach. The data collection technique uses the survey method with questionnaires distributed online via Whatsapp social media, which is made via the Google form. Data analysis was performed on SmartPLS software version 3.3.9. The results of the data analysis show that entrepreneurship education and the environment each have a positive but not significant effect on entrepreneurial intentions. Entrepreneurial attitude has a positive and significant effect on entrepreneurial intentions.